Об особенностях перевода В. Брюсова на русский язык поэмы «Абу-Лала Маари » - Габриелян, Любовь
Avetik Isahakyan's poem ,,Abool-Ala Mahari,, (1910) is the masterpiece of the Armenian literature translated into many languages of the world. The poem was created in the crucial period of the poet's life, just before his long-term departure from the Motherland where he might be imprisoned for his active participation in the national-liberation movement of the Armenians. The great creator's dramatic feelings of the collision with the social system have been brilliantly expressed in the poem ,,Abool-Ala-Mahari,,. Ավետիք Իսահակյանի ,,Աբու-Լալա-Մահարի,, պոեմը հայ գրականության գլուխգործոցներից է: Այն թարգմանված է աշխարհի տարբեր լեզուներով: Պոեմը գրվել է գրողի կյանքի բախտորոշ ժամանակաշրջանում, երբ նա ստիպված էր հեռանալ իր հայրենիքից, որտեղ նրան դատապարտել էին ազատազրկման` ազգային ազատագրական պայքարին մասնակցելու համար: Պոեմում վառ արտացոլված է գրողի անհատական հոգևոր զգացմունքների և սոցիալական հասարակարգի միջև ողբերգական առճակատումը: В статье рассмотрена тема - чрезвычайно важной роли художественного перевода в современном мире. Перевод как фактор взаимодействия культур.
Keywords: Языкознание